Post-processing method and system for selective laser melting additive manufacturing component
By melting additively manufactured titanium alloy samples in laser selection areas, combining heat treatment, stamping treatment and annealing treatment, the problem of insufficient hardness and corrosion resistance in the post-treatment of additive manufacturing is solved, and rapid and low-cost performance improvement is achieved.
Patent Information
- Application Number
- CN202510058485.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-08
AI Technical Summary
During the laser selection melting additive manufacturing process, titanium alloy materials form complex microstructure due to their high thermal conductivity and easy hydrogen absorption properties, resulting in high brittleness, low plasticity and significant residual stresses, affecting their corrosion resistance and reliability.
A post-treatment method for melting additive manufacturing components in laser selection zones is adopted. By obtaining the initial ratio of α phase and β phase in the titanium alloy sample, heat treatment parameters and stamping parameters are obtained based on the preset phase change parameter mapping table, heat treatment and stamping treatment are performed, and then annealing is performed to improve the hardness and corrosion resistance of the titanium alloy sample.
This method effectively improves the hardness and corrosion resistance of titanium alloy samples, and has the characteristics of rapid and low cost, and can improve the comprehensive mechanical properties of titanium alloy samples without increasing complexity.
Smart Images

Figure CN119772208A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of additive manufacturing post-processing, and in particular to a post-processing method and system for a component manufactured by additive manufacturing using laser selective melting. Background Art
[0002] Titanium alloy materials have been widely used in aerospace, medical implants and other high-performance applications due to their excellent strength-to-weight ratio, good corrosion resistance and biocompatibility. However, during the selective laser melting (SLM) additive manufacturing process, due to the high thermal conductivity and easy hydrogen absorption of titanium alloys, the molten pool solidifies rapidly, forming a complex microstructure, such as a large amount of α phase and a small amount of β phase. This microstructure not only causes the titanium alloy specimens manufactured by SLM to exhibit high brittleness, low plasticity and anisotropy, but also produces significant residual stress. These characteristics make titanium alloy materials more fragile in corrosive environments, especially in specific application scenarios with extremely strict requirements on corrosion resistance, which seriously affects the performance and reliability of titanium alloy parts. For example, marine engineering allows a certain degree of porosity in non-critical areas, but they must be able to resist corrosion caused by seawater, salt spray and other marine environmental factors. Even if there is a small amount of porosity in the internal structure of chemical processing and storage equipment, it will not significantly affect its functionality, but if the material does not have sufficient corrosion resistance, it may cause leakage or other safety accidents.
[0003] In order to ensure the long-term stability and reliability of the material in various harsh environments, post-processing methods are usually used. Hot isostatic pressing (HIP) technology is effective in the post-processing of titanium alloy samples. It can not only improve the density of titanium alloy samples, but also optimize their microstructure, thereby improving various properties including corrosion resistance. For example, the Chinese invention patent with application publication number CN 116275041 A discloses a method for reducing residual stress of additively manufactured high-temperature alloys based on hot isostatic pressing, comprising the following steps: 1) placing the additively manufactured high-temperature alloy in a hot isostatic pressing furnace and evacuating the vacuum. When the vacuum degree is 10 -3 -10 -4 Pa: turn off the vacuum pump, introduce inert gas into the hot isostatic pressing furnace, and heat the additively manufactured high-temperature alloy to a first preset hot isostatic pressing temperature; 2) keep the additively manufactured high-temperature alloy at the first preset hot isostatic pressing temperature and the first pressure for a first set time; then heat the additively manufactured high-temperature alloy to a second preset hot isostatic pressing temperature, and keep it at the second preset hot isostatic pressing temperature and the second pressure for a second set time; after cooling treatment, obtain the high-temperature alloy after hot isostatic pressing treatment.
[0004] However, hot isostatic pressing equipment is expensive and has a long processing cycle, usually taking several hours or even dozens of hours, which is a huge bottleneck for large-scale production and limits its widespread application in the post-processing of titanium alloys manufactured by laser selective melting additive manufacturing. This makes the post-processing of titanium alloys prepared by SLM face the dual challenges of efficiency and cost, making it difficult to improve the performance of titanium alloy samples efficiently and economically. Summary of the invention
[0005] The main purpose of the present invention is to provide a post-processing method and system for laser selective melting additive manufacturing components. In order to solve the above-mentioned technical problems, the present invention specifically adopts the following technical solutions: A first aspect of the present invention is to provide a post-processing method for a component manufactured by selective laser melting additive manufacturing, the method comprising: S101 obtains the initial ratio of α phase and β phase in the titanium alloy sample obtained by laser selective melting additive manufacturing; S102, based on a preset phase change parameter mapping table, obtaining heat treatment parameters and stamping processing parameters according to the initial ratio of the α phase and the β phase, wherein the preset phase change parameter mapping table includes: a data table of changes in the ratio of the α phase and the β phase in the titanium alloy under different heat treatment parameters and different stamping processing parameters, the heat treatment parameters include heating temperature and heat preservation time; the heating temperature belongs to the preset phase change temperature threshold range; S103: placing the titanium alloy sample in a heat treatment zone, heating the titanium alloy sample according to the heating temperature, and when the titanium alloy sample is placed in the heat treatment zone for a time period that reaches the heat preservation time period, transferring the titanium alloy sample from the heat treatment zone to a stamping treatment zone; S104, during the process of transferring the titanium alloy sample from the heat treatment zone to the stamping treatment zone, detecting the actual temperature of the titanium alloy sample; S105 When the actual temperature reaches the heating temperature, the titanium alloy sample is stamped in the stamping area according to the stamping parameters, and the stamped titanium alloy sample is annealed to obtain a target titanium alloy sample, wherein a target ratio of α phase to β phase in the target titanium alloy sample is lower than the initial ratio.
[0006] In some embodiments, the method further includes: when the actual temperature is lower than the heating temperature, calculating a first temperature difference between the actual temperature and the heating temperature; determining supplementary heat treatment parameters according to the first temperature difference, the supplementary heat treatment parameters including a supplementary heating temperature and a supplementary insulation time; placing the titanium alloy sample in a heat treatment zone, heating the titanium alloy sample according to the supplementary heating temperature, and when the titanium alloy sample is placed in the heat treatment zone for a period of time that reaches the supplementary insulation time, transferring the titanium alloy sample from the heat treatment zone to the stamping treatment zone; executing step S104.
[0007] In some embodiments, the method also includes: when the actual temperature is higher than the heating temperature, calculating a second temperature difference between the actual temperature and the heating temperature; when the second temperature difference is within a first difference threshold, adjusting the stamping processing parameters based on the actual temperature to obtain target stamping processing parameters, and the target stamping processing parameters are lower than the stamping processing parameters; and stamping the titanium alloy sample in the stamping processing area according to the target stamping processing parameters to obtain a target titanium alloy sample.
[0008] In some embodiments, the S104 also includes: calculating the total oxygen content required to be supplied based on the surface area of the titanium alloy sample and the preset oxide layer thickness; obtaining the corresponding low-oxygen mixed gas based on the preset ratio of oxygen and inert gas and the total oxygen content; and supplying the low-oxygen mixed gas to the titanium alloy sample in the transfer path of the titanium alloy sample from the heat treatment zone to the stamping treatment zone.
[0009] In some embodiments, the method further includes: when the second temperature difference is greater than the first difference threshold and less than the second difference threshold, before supplying the low oxygen mixed gas to the titanium alloy sample, performing low temperature treatment on the low oxygen mixed gas so that the low oxygen mixed gas reaches a preset temperature.
[0010] In some embodiments, the stamping process parameters include stamping rate, stamping pressure, and holding time; wherein, the stamping rate is 300 mm / s to 500 mm / s, the stamping pressure is 10 MPa, and the holding time is 10 s.
[0011] In some embodiments, the preset phase change temperature threshold is 980°C to 1200°C.
[0012] In some embodiments, the temperature of the titanium alloy sample is adjusted to a first preset annealing temperature threshold, and maintained for a preset annealing time, and the titanium alloy sample is annealed at a preset cooling rate to obtain the target titanium alloy sample.
[0013] In some embodiments, the temperature of the titanium alloy sample is adjusted to a second preset annealing temperature threshold, and is kept at a third preset annealing temperature threshold for a preset annealing time, and the titanium alloy sample is cooled for annealing to obtain the target titanium alloy sample, wherein the second preset annealing temperature threshold is higher than the third preset annealing temperature threshold.
[0014] A second aspect of the present invention is to provide a post-processing system for a component manufactured by selective laser melting additive manufacturing, the system comprising: A sample acquisition module is used to obtain the initial ratio of α phase and β phase in the titanium alloy sample obtained by laser selective melting additive manufacturing; A processing parameter module, for obtaining heat treatment parameters and stamping processing parameters according to the initial ratio of the α phase and the β phase based on a preset phase change parameter mapping table, wherein the preset phase change parameter mapping table includes: a data table of the change in the ratio of the α phase and the β phase in the titanium alloy under different heat treatment parameters and different stamping processing parameters, the heat treatment parameters include heating temperature and holding time; the heating temperature belongs to the preset phase change temperature threshold range; A heating treatment module, used for placing the titanium alloy sample in a heat treatment zone, heating the titanium alloy sample according to the heating temperature, and transferring the titanium alloy sample from the heat treatment zone to a stamping treatment zone when the placement time of the titanium alloy sample in the heat treatment zone reaches the insulation time; A sample transfer module, used for detecting the actual temperature of the titanium alloy sample during the transfer process of the titanium alloy sample from the heat treatment area to the stamping treatment area; A stamping processing module is used to, when the actual temperature reaches the heating temperature, perform stamping processing on the titanium alloy sample in the stamping processing area according to the stamping processing parameters, and perform annealing processing on the titanium alloy sample after the stamping processing to obtain a target titanium alloy sample, wherein the target ratio of α phase to β phase in the target titanium alloy sample is lower than the initial ratio.
[0015] Beneficial technical effects: The present invention provides a post-processing method for titanium alloy prepared by SLM, which can effectively improve the hardness and corrosion resistance of titanium alloy samples, and has the characteristics of fastness and low cost. The heat treatment parameters and stamping processing parameters in the post-processing process are finely set, and the β phase content in the microstructure is increased by heat treatment, so that the titanium alloy sample after heating can reach the expected microstructure, thereby improving the corrosion resistance of the titanium alloy sample; and through real-time temperature monitoring of the adaptability of the heat treatment parameters and stamping processing parameters in actual applications, a dynamic control mechanism is provided to ensure high coordination between the two processing processes; hot stamping treatment is performed on the titanium alloy sample, which significantly improves the hardness of the titanium alloy sample and reduces the residual stress inside the titanium alloy sample; annealing treatment is then performed to further improve the corrosion resistance of the titanium alloy sample, and the residual stress inside the titanium alloy sample is reduced again. On the whole, the problem of hardness loss caused by annealing heat treatment is overcome by hot stamping, thereby comprehensively improving the comprehensive mechanical properties such as hardness and corrosion resistance of the titanium alloy sample.
[0016] First, by pre-setting the phase change parameter mapping table, the heat treatment parameters and stamping processing parameters are selected according to the initial α-phase and β-phase ratio of each titanium alloy sample to ensure a high degree of parameter matching between the two processing flows and to precisely control the phase composition. At the same time, personalized treatment is performed for different batches or categories of titanium alloy samples to ensure the consistency of the microstructure and mechanical properties of the titanium alloy samples to meet the needs of mass production and quality control.
[0017] Secondly, after the heat treatment is completed, during the transfer from the heat treatment area to the stamping treatment area, the actual temperature of the titanium alloy sample is monitored to verify the adaptability of the heat treatment parameters and the stamping treatment parameters in actual applications. When the adaptability is low, the dynamic adjustment mechanism is triggered to flexibly respond to the temperature error, so that the heat treatment parameters and the stamping treatment parameters form a tightly coupled and dynamically interactive relationship through the actual temperature of the titanium alloy sample after heat treatment, ensuring that the titanium alloy sample is only stamped under the optimal state, avoiding the phase composition not meeting expectations due to low temperature, and the organizational changes or deformation of the titanium alloy sample due to high temperature. Specifically, the dynamic adjustment mechanism includes: compensatory heating, when the actual temperature is lower than the heating temperature, the titanium alloy sample is placed back in the heat treatment area for compensatory heating, so that the temperature of the titanium alloy sample is heated to a suitable range, ensuring that the heating treatment achieves the expected effect; stamping treatment parameter adjustment, when the actual temperature is higher than the heating temperature and the temperature difference is within the first difference threshold, the stamping treatment parameters are fine-tuned according to the actual temperature to ensure that the titanium alloy sample is stamped under the optimal state.
[0018] In addition, a low-oxygen mixed gas is supplied to the titanium alloy sample in the transfer path, and a large amount of inert gas (such as argon and helium) forms a protective barrier around the titanium alloy sample, effectively isolating the oxygen in the air and other components that may cause adverse reactions, ensuring that only a preset proportion of trace oxygen can contact the surface of the titanium alloy and react to form a dense and stable titanium oxide film. This oxide film can effectively prevent further oxidation and corrosion, play a good protective role, and achieve controllable oxidation. Furthermore, when the temperature difference is large, the titanium alloy sample is subjected to low-temperature treatment by a low-oxygen mixed gas in a low-temperature state. While the oxidation is controlled, the actual temperature of the titanium alloy sample is accelerated to drop to the heating temperature to ensure the stamping treatment effect.
[0019] Finally, after the stamping process, the titanium alloy sample is annealed to effectively reduce the residual stress accumulated inside the titanium alloy sample, improve the corrosion resistance and dimensional stability of the titanium alloy sample, and thereby improve the dimensional stability and service life of the parts. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. In all the drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, each element or part is not necessarily drawn according to the actual scale. Obviously, the drawings described below are some embodiments of the present invention. For those of ordinary skill in the art, other drawings can also be obtained based on these drawings without paying creative labor.
[0021] Figure 1 It is a schematic flow chart of a post-processing method of a component manufactured by selective laser melting additive manufacturing according to an embodiment of the present invention; Figure 2 It is a schematic diagram of a post-processing process of a component manufactured by selective laser melting additive manufacturing provided by an embodiment of the present invention; Figure 3 is a schematic diagram comparing the effects of titanium alloy samples provided by an embodiment of the present invention under different post-treatment conditions; Figure 4 is a graph showing the hardness test results of titanium alloy samples under different post-treatment conditions provided by an embodiment of the present invention; Figure 5 is a graph showing corrosion test results of titanium alloy samples under different post-treatment conditions provided by an embodiment of the present invention; Figure 6 It is a schematic block diagram of a post-processing system for a component manufactured by laser selective melting additive manufacturing provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0023] Herein, suffixes such as "module", "component" or "unit" used to represent elements are only used to facilitate the description of the present invention, and have no specific meanings by themselves. Therefore, "module", "component" or "unit" can be used mixedly.
[0024] In this document, the terms "upper", "lower", "inner", "outer", "front", "back", "one end", "the other end" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the devices or elements referred to must have a specific orientation, be constructed and operate in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance.
[0025] In this document, unless otherwise clearly specified and limited, the terms "installed", "provided with", "connected", etc. should be understood in a broad sense. For example, "connected" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, a direct connection, or an indirect connection through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0026] Herein "and / or" includes any and all combinations of one or more of the associated listed items.
[0027] Herein, "plurality" means two or more than two, ie, it includes two, three, four, five, etc.
[0028] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.
[0029] Titanium alloys are widely used in a variety of fields such as aerospace, medical and automotive due to their excellent strength-to-weight ratio, corrosion resistance and biocompatibility. Its microstructure is mainly composed of two phases: α phase and β phase, which play a key role in determining the properties of titanium alloys. The α phase has a close-packed hexagonal crystal structure and is the most common phase in titanium alloys. It provides high yield strength and tensile strength, and due to its tightly packed atomic arrangement, the density of the α phase is relatively low, which helps to reduce the weight of the material. However, compared with the β phase, the α phase has poor plasticity and is prone to brittle fracture. In contrast, the β phase has a body-centered cubic crystal structure, which exhibits excellent corrosion resistance, especially for chemical attack in certain specific environments. More importantly, the mechanical properties of the β phase are relatively consistent in all directions, that is, isotropic, which is very beneficial for some applications that require high material uniformity.
[0030] The ratio of α phase and β phase in titanium alloy specimens prepared by SLM is not fixed, but varies according to specific conditions. For example, Ti-6Al-4V, which is commonly used in titanium alloys, is mainly composed of titanium, aluminum and vanadium. During the SLM process, rapid cooling inhibits the transformation of β phase to α phase, resulting in more β phase directly transforming into martensitic α' phase (an undercooled α phase), resulting in a large amount of α phase in the final titanium alloy specimen, while β phase is relatively small. This microstructure gives the titanium alloy specimen the characteristics of high strength, low plasticity and high brittleness, and its corrosion resistance is also lower than that of the forged state.
[0031] In order to improve this situation, in addition to the post-treatment method of hot isostatic pressing, a coating can be added to the surface of the titanium alloy to form a protective film to improve corrosion resistance. However, the coating is prone to cracking or falling off during use, especially under high mechanical stress or harsh environmental conditions, which seriously affects the long-term reliability and durability of the coating.
[0032] It can be seen that the existing post-processing technology generally performs poorly in terms of efficiency, cost-effectiveness and long-term stability. Whether it is the reliability problem of coating technology or the high cost and long time of HIP, it cannot fully meet the industrial needs of efficiency, economy and reliability, limiting the overall improvement of the performance of SLM titanium alloy parts.
[0033] Therefore, the present invention provides a post-processing method for titanium alloy prepared by SLM, which can effectively improve the hardness and corrosion resistance of titanium alloy samples quickly and at low cost. The heat treatment parameters and stamping processing parameters in the post-processing process are finely set, and the β phase content in the microstructure is increased by heat treatment, so that the titanium alloy sample after heating can achieve the expected microstructure, thereby improving the corrosion resistance of the titanium alloy sample; and through real-time temperature monitoring of the adaptability of the heat treatment parameters and stamping processing parameters in actual applications, a dynamic control mechanism is provided to ensure high coordination between the two processing processes; hot stamping treatment is performed on the titanium alloy sample, which significantly improves the hardness of the titanium alloy sample and reduces the residual stress inside the titanium alloy sample; annealing treatment is then performed to further improve the corrosion resistance of the titanium alloy sample, and the residual stress inside the titanium alloy sample is reduced again. On the whole, the problem of hardness loss caused by annealing heat treatment is overcome by hot stamping, thereby comprehensively improving the comprehensive mechanical properties such as hardness and corrosion resistance of the titanium alloy sample.
[0034] Some embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. The following embodiments and features of the embodiments can be combined with each other without conflict. Figure 1 , Figure 1 is a schematic flow chart of a post-processing method for a component manufactured by laser selective melting additive manufacturing according to an embodiment of the present invention, such as Figure 1 As shown, an embodiment of the present invention provides a post-processing method for a component manufactured by selective laser melting additive manufacturing, and the method includes S101 to S105.
[0035] S101 obtains the initial ratio of α phase to β phase in the titanium alloy sample obtained by laser selective melting additive manufacturing.
[0036] Specifically, the titanium alloy sample can be subjected to microstructural analysis to determine the initial ratio of the α phase to the β phase in the titanium alloy sample. For example, metallographic microscope observation, X-ray diffraction analysis, electron backscatter diffraction, transmission electron microscopy and other experimental methods can determine the initial ratio of the α phase to the β phase.
[0037] It should be understood that a systematic experimental design and data analysis method can be used for a batch of titanium alloy specimens or a class of titanium alloy specimens to avoid repeated microscopic observations of each sample. On the premise of consistency in the performance of the titanium alloy specimens, the need for repeated microscopic observations and other complex analyses can be greatly reduced, thereby improving work efficiency and reducing costs. At the same time, the titanium alloy specimens obtained after heat treatment can achieve the expected microstructure.
[0038] For example, several representative titanium alloy samples are selected from a batch for detailed analysis. For example, early, middle and late titanium alloy samples are taken from the same batch to cover the entire production batch to ensure the comprehensiveness and representativeness of the results. The initial ratio range of α phase and β phase in the titanium alloy samples in the batch is determined and organized into a database. Subsequently, only relevant data needs to be obtained from the database.
[0039] S102 obtains heat treatment parameters and stamping processing parameters based on the preset phase change parameter mapping table according to the initial ratio of the α phase and the β phase, wherein the preset phase change parameter mapping table includes: a data table of the change in the proportion of the α phase and the β phase in the titanium alloy under different heat treatment parameters and different stamping processing parameters, the heat treatment parameters include heating temperature and insulation time; the heating temperature belongs to the preset phase change temperature threshold range.
[0040] Specifically, according to the initial ratio of the α phase and the β phase, the closest initial condition is found in the preset phase change parameter mapping table, and corresponding to the initial condition, the recommended heat treatment parameters and stamping processing parameters are found, which can achieve the expected phase composition adjustment and performance optimization. It should be understood that by presetting the phase change parameter mapping table, the heat treatment parameters and stamping processing parameters are selected according to the initial α phase and β phase ratio of each titanium alloy sample, and the heat treatment parameters and stamping processing parameters in the post-processing process can be quickly and finely set to ensure that the parameters between the two processing flows are highly matched, and the phase composition is accurately controlled. At the same time, personalized treatment is performed for different batches or categories of titanium alloy samples to ensure the consistency of the microstructure and mechanical properties of the produced titanium alloy samples to meet the needs of mass production and quality control.
[0041] Among them, the preset phase change parameter mapping table is used to quickly select the optimal processing parameters according to the initial ratio of α phase and β phase to achieve the expected material properties. Through experimental verification and data analysis, the heat treatment parameters and stamping processing parameters can be continuously optimized under different initial conditions. For example, for a specific heat treatment parameter combination, the corresponding optimal stamping processing parameter combination is found to ensure a high degree of match between the two, and a data table of the change in the ratio of α phase and β phase in titanium alloy under different heat treatment parameters and different stamping processing parameters is obtained. Therefore, the relationship between the change in the ratio of α phase and β phase in the titanium alloy sample is regulated by specific heat treatment parameters, and the hardness of the titanium alloy sample is improved in combination with the stamping processing parameters.
[0042] In some embodiments, the preset phase change parameter mapping table also includes a heat loss table of the titanium alloy sample changing with time after leaving the heating environment (such as the heat treatment zone). The heat treatment parameters can be appropriately adjusted according to the heat loss corresponding to the time spent in the process of transferring from the heat treatment zone to the stamping treatment zone in the actual scenario. For example, in the batch post-processing process, it takes 2 minutes to transfer all the titanium alloy samples, and the temperature is expected to drop by 10°C. Then, the heating temperature in the heat treatment parameters is increased by 10°C, thereby further accurately controlling the heat treatment parameters and stamping processing parameters in the post-processing process. Among them, the cooling rate of the titanium alloy sample at room temperature will vary due to many factors, including part size, shape, ambient temperature and air flow conditions, so that the temperature loss data of different types of titanium alloy samples can be obtained, and then the heat loss table can be obtained based on these temperature loss data.
[0043] It should be understood that the heat treatment parameters determine the microstructure and mechanical properties of the titanium alloy specimen, while the stamping processing parameters are used to optimize the hardness performance of the titanium alloy specimen while maintaining the above microstructure and mechanical properties. The two work together to achieve the best microstructure and mechanical properties. At the same time, in order to ensure the stamping effect and avoid deformation of the titanium alloy specimen, the heat treatment parameters and stamping processing parameters must be highly matched to avoid uneven stress distribution inside the titanium alloy specimen due to mismatched post-processing parameters, which may cause unnecessary plastic deformation or cracks.
[0044] Among them, heat treatment parameters refer to a series of key conditions that control and affect the microstructure and properties of titanium alloy samples during the heat treatment process. These parameters determine the occurrence, degree and final mechanical properties of the internal phase change of the titanium alloy sample. Exemplarily, the heat treatment parameters include heating temperature and holding time. The heating temperature is the highest temperature to which the sample is heated during the heat treatment process or the ambient temperature of the heat treatment area. The heating temperature determines the occurrence and degree of phase change; the holding time is the time the titanium alloy sample is kept at the heating temperature, or the time the titanium alloy sample is placed in the heat treatment area after being heated to the heating temperature. The holding time ensures that the phase change is fully carried out, so that the internal temperature distribution of the titanium alloy sample is uniform, thereby promoting the stable formation of the new phase.
[0045] The preset phase transition temperature threshold is determined based on the transition temperature from the α phase to the β phase and the influence range of the β stabilizing element content. Exemplarily, the preset phase transition temperature threshold is 980°C to 1200°C.
[0046] When the temperature of the titanium alloy sample exceeds 980℃, the α phase in the titanium alloy sample begins to transform into the β phase. Therefore, 980℃ is the lowest temperature that promotes the formation of the β phase. Further heating the titanium alloy sample to below 1200℃ can accelerate the phase change and homogenization process without causing excessive dissolution or volatilization, while avoiding abnormal grain growth (grain coarsening) caused by overheating of the titanium alloy sample (for example, above 1200℃). Coarse grains will lead to decreased corrosion resistance. Therefore, within this temperature range, the β phase content in the titanium alloy sample can be effectively increased, which is beneficial to improving the corrosion resistance of the titanium alloy sample. While ensuring the full occurrence of the α to β phase transformation, the chemical stability of the titanium alloy sample can be maintained, and the internal microstructure of the titanium alloy sample can be ensured to be fine and evenly distributed, thereby maintaining good mechanical properties.
[0047] Among them, stamping processing parameters refer to a series of key conditions for optimizing the internal microstructure and mechanical properties of titanium alloy specimens by applying controlled pressure without changing the shape of the titanium alloy specimens. These parameters are intended to activate beneficial deformation mechanisms in the material, such as plastic flow, grain refinement, recrystallization, etc., thereby improving the material's performance indicators such as strength, corrosion resistance and fatigue life. Exemplarily, stamping processing parameters include stamping rate, stamping pressure, and holding time.
[0048] The punching rate is the speed at which pressure is applied, that is, the degree of pressure increase per unit time, which is used to control the distribution of internal stress and strain hardening behavior of titanium alloy specimens. Appropriate punching rate can optimize the microstructure, reduce residual stress, and improve the uniformity of titanium alloy specimens.
[0049] The stamping pressure is the maximum force or pressure applied during the stamping process, which is used to introduce beneficial plastic deformation inside the titanium alloy sample without significantly changing its external shape. Appropriate stamping pressure can activate dislocation movement in the titanium alloy sample, promote grain refinement and recrystallization, and thus improve the strength of the titanium alloy sample; suitable pressure can also eliminate internal pores and improve the density of the titanium alloy sample.
[0050] The holding time is the time to maintain the pressure after stamping is completed, ensuring that the pressure is fully transmitted and maintained for a sufficient time inside the titanium alloy specimen to achieve the expected microstructural changes. A longer holding time helps to evenly distribute the stress inside the titanium alloy specimen and reduce local stress concentration. This helps to improve the overall performance of the titanium alloy specimen, such as corrosion resistance and fatigue life.
[0051] Exemplarily, the stamping processing parameters include stamping rate, stamping pressure, and holding time; wherein the stamping rate is 300mm / s to 500mm / s, the stamping pressure is 10MPa, and the holding time is 10s. Through refined control of stamping processing parameters, the titanium alloy sample can be effectively stamped, the hardness of the titanium alloy sample can be optimized, and at the same time, the organizational changes or deformation of the titanium alloy sample can be avoided, and the corrosion resistance of the titanium alloy sample can be improved, thereby comprehensively improving the comprehensive mechanical properties of the titanium alloy sample, such as hardness and corrosion resistance.
[0052] S103 places the titanium alloy sample in a heat treatment zone, heats the titanium alloy sample according to the heating temperature, and when the titanium alloy sample is placed in the heat treatment zone for a time period that reaches the heat preservation time period, transfers the titanium alloy sample from the heat treatment zone to the stamping treatment zone. The time period for which the titanium alloy sample is placed in the heat treatment zone may be the time period for which the titanium alloy sample is kept at the heating temperature of the heat treatment zone, or the time period for which the titanium alloy sample is placed in the heat treatment zone after being heated to the heating temperature.
[0053] For example, see Figure 2 , Figure 2 is a schematic diagram of a post-processing process of a laser selective melting additive manufacturing component provided by an embodiment of the present invention, such as Figure 2 As shown, according to the heating temperature in the preset phase change parameter mapping table, the titanium alloy sample 10 is placed in the heat treatment zone 20 for heating. When the insulation time is reached, automated equipment, such as a robotic arm 301, can be used to quickly transfer the titanium alloy sample 10 from the heat treatment zone 20 to the stamping treatment zone 40, thereby improving the efficiency of post-processing and reducing human errors, so as to ensure that the temperature loss of the titanium alloy sample during the transfer process is minimized to maintain the desired microstructural changes.
[0054] It should be noted that the heat treatment zone is used to heat treat the titanium alloy specimens, and specifically can be a heat treatment furnace, such as a vacuum heat treatment furnace, a resistance furnace, or a gas furnace. Other types of equipment or technologies can also be used to achieve heating and insulation of the titanium alloy specimens, which is not limited here. The stamping treatment zone is used to press the titanium alloy specimens after heat treatment, and can be a hydraulically driven stamping equipment or a mechanically driven stamping equipment, which is not limited here. The heat treatment zone and the stamping treatment zone can be integrated into the same device, and the titanium alloy specimens can be moved between different areas by a robotic arm. The heat treatment zone and the stamping treatment zone can also be two independent devices, and the robotic arm is responsible for transferring the titanium alloy specimens between the two, which is not limited here.
[0055] In some embodiments, the heat treatment area is preheated to a predetermined temperature (e.g., 980°C) to reduce stress concentration caused by temperature difference, and the working state of the stamping treatment area is pre-checked to ensure that it is in good condition and ready for subsequent processing. Furthermore, during the heating process, the heating rate is ensured to be stable to avoid thermal shock caused by rapid temperature rise.
[0056] In some embodiments, the titanium alloy samples may be heated in batches to ensure that the titanium alloy samples are evenly distributed in the heat treatment zone to avoid local overheating or uneven cooling.
[0057] S104: During the transfer process of the titanium alloy sample from the heat treatment zone to the stamping treatment zone, the actual temperature of the titanium alloy sample is detected.
[0058] For example, Figure 2 As shown, the gripping part of the robot arm 301 is provided with a temperature detection device, and the actual temperature of the titanium alloy sample 10 is detected by the temperature detection device during the process of the robot arm 301 gripping the titanium alloy sample 10 and transferring it from the heat treatment area 20 to the stamping treatment area 40. In another example, the titanium alloy sample is gripped by a gripping device manually and transferred from the heat treatment area to the stamping treatment area, and the gripping device is provided with a temperature detection device, and the actual temperature of the titanium alloy sample is detected by the temperature detection device.
[0059] S105 When the actual temperature reaches the heating temperature, the titanium alloy sample is stamped in the stamping area according to the stamping parameters, and the stamped titanium alloy sample is annealed to obtain a target titanium alloy sample, wherein a target ratio of α phase to β phase in the target titanium alloy sample is lower than the initial ratio.
[0060] Specifically, after the heat treatment is completed, during the transfer from the heat treatment area to the stamping treatment area, the actual temperature of the titanium alloy sample is monitored to verify the adaptability of the heat treatment parameters and the stamping treatment parameters in actual applications. When the actual temperature reaches the heating temperature, the heat treatment parameters and the stamping treatment parameters maintain a high degree of adaptability, and the pre-acquired stamping treatment parameters can be directly used to stamp the titanium alloy sample to improve the hardness of the titanium alloy sample. After the stamping treatment is completed, the stamped titanium alloy sample is annealed to reduce the residual stress in the titanium alloy sample, while further improving the corrosion resistance of the titanium alloy sample to obtain the target titanium alloy sample. For example, Figure 2As shown, after the stamping process of the titanium alloy sample 10 in the stamping process area 40 is completed, the titanium alloy sample 10 is clamped by the mechanical arm 302 and transferred from the stamping process area 40 to the annealing process area 50. Among them, the mechanical arm 301 and the mechanical arm 302 can be the same structure or different structures, which is not limited here. In another example, the titanium alloy sample is manually clamped by a clamping device and transferred from the stamping process area to the annealing process area.
[0061] It should be understood that the target titanium alloy sample obtained by post-treatment has increased the β phase content in the microstructure through heating treatment, thereby improving the corrosion resistance of the titanium alloy sample; the hardness of the titanium alloy sample is significantly improved by hot stamping treatment of the titanium alloy sample, while maintaining the β phase content in the microstructure of the titanium alloy sample, and then annealing treatment is performed to further improve the corrosion resistance of the titanium alloy sample, overcoming the problem of hardness loss caused by annealing heat treatment, thereby comprehensively improving the comprehensive mechanical properties of the titanium alloy sample such as hardness and corrosion resistance.
[0062] The embodiment of the present invention adopts controlled cooling to perform annealing treatment, and controls the cooling rate to influence the development of the microstructure. Slow cooling can promote a uniform α and β two-phase structure, which usually has good corrosion resistance, while avoiding stress concentration and adverse phase changes caused by too fast cooling, thereby reducing the possibility of cracks and other defects and preventing these defects from becoming corrosion paths.
[0063] In some embodiments, the S105 further includes: adjusting the temperature of the titanium alloy sample to a first preset annealing temperature threshold, maintaining the temperature for a preset annealing time, and annealing the titanium alloy sample at a preset cooling rate to obtain the target titanium alloy sample.
[0064] Specifically, the titanium alloy sample is not completely cooled down after the stamping process is completed, so the temperature of the titanium alloy sample is appropriately adjusted (heated or cooled) to a lower first preset annealing temperature threshold, and then slowly cooled after keeping warm for a certain period of time. Thus, while the annealing heat improves corrosion resistance, it reduces or eliminates the residual stress generated during the processing, prevents deformation or cracking of parts, and improves dimensional stability. Among them, the first preset annealing temperature threshold can be 450℃ to 650℃, 510℃ to 700℃, the preset annealing time is used to achieve a uniform temperature distribution inside the titanium alloy sample, and the preset cooling rate is used to limit the slow cooling of the titanium alloy sample. The specific values can be flexibly adjusted according to the cross-sectional size of the titanium alloy sample, the processing history and the degree of stress elimination required, and are not limited here.
[0065] In some embodiments, the S105 also includes: adjusting the titanium alloy sample to a second preset annealing temperature threshold, and keeping it warm at a third preset annealing temperature threshold for a preset annealing time, cooling the titanium alloy sample for annealing, and obtaining the target titanium alloy sample, wherein the second preset annealing temperature threshold is higher than the third preset annealing temperature threshold.
[0066] Specifically, the titanium alloy sample is not completely cooled down after the stamping process is completed. Therefore, the temperature of the titanium alloy sample is appropriately adjusted (heated or cooled) to a higher temperature where recrystallization occurs, and then transferred to a low temperature for heat preservation, and then slowly cooled to room temperature. While the annealing heat improves corrosion resistance, it effectively promotes recrystallization and phase transformation, refines grains, reduces brittleness and anisotropy problems, and effectively eliminates residual stress in steel parts. Among them, the second preset annealing temperature threshold can be 20-160°C below the transformation temperature of the β phase in the titanium alloy sample, and the third preset annealing temperature threshold can be 600-650°C. The preset annealing time is used to achieve a uniform temperature distribution inside the titanium alloy sample. The specific value can be flexibly adjusted according to the cross-sectional size of the titanium alloy sample, the processing history and the degree of stress elimination required, and is not limited here.
[0067] For example, Figure 2 The mechanical arm 302 shown has the same structure as the mechanical arm 301, or the gripping portion of the mechanical arm 302 is also provided with a temperature detection device. In the process of the mechanical arm 302 gripping the titanium alloy sample 10 and transferring it from the stamping treatment area 40 to the annealing treatment area 50, the actual temperature of the titanium alloy sample is detected by the temperature detection device, and the working parameters of the annealing treatment area are determined according to the actual temperature, so that the actual temperature of the titanium alloy sample is adjusted to the first preset annealing temperature threshold or the second preset annealing temperature threshold. In another example, the titanium alloy sample is manually gripped by a gripping device and transferred from the heat treatment area to the stamping treatment area. The gripping device is provided with a temperature detection device, and the actual temperature of the titanium alloy sample is detected by the temperature detection device.
[0068] See also Figure 3 , Figure 3 is a schematic diagram comparing the effects of titanium alloy samples provided by the embodiment of the present invention under different post-treatment conditions, such as Figure 3As shown in the figure, the effects under different post-treatment conditions are displayed under a field of view of 50 microns (μm). (a) in the figure is the effect of simple annealing treatment, in which the α phase content is 99.5% and the β phase content is 0.158%; (b) in the figure is the effect of stamping when the actual temperature is lower than the heating temperature, in which the α phase content is 99.59% and the β phase content is 0.41%; (c) in the figure is the effect of stamping when the actual temperature reaches the heating temperature, in which the α phase content is 99.26% and the β phase content is 0.74%; (d) in the figure is the effect of stamping when the actual temperature reaches the heating temperature and annealing treatment is performed, in which the α phase content is 99.28% and the β phase content is 0.72%.
[0069] It can be seen that although the β-phase content in the titanium alloy sample without annealing after high-temperature stamping is slightly higher, after annealing, the β-phase content in the titanium alloy sample in Figure (d) is significantly higher than that in other post-treatment conditions, and its microstructure helps to evenly distribute stress throughout the titanium alloy sample, reducing local stress concentration. In addition, annealing treatment also improves the corrosion resistance of the titanium alloy sample to a certain extent, thereby optimizing the overall performance of the titanium alloy sample, not only maintaining good mechanical properties such as corrosion resistance and fatigue life, but also further improving these properties.
[0070] See also Figures 4 to 5 , Figure 4 is a graph showing the hardness test results of titanium alloy samples under different post-treatment conditions provided by an embodiment of the present invention, Figure 5 1 is a graph showing the corrosion test results of titanium alloy samples under different post-treatment conditions provided in an embodiment of the present invention.
[0071] like Figure 4 The average microhardness of Ti6Al4V titanium alloy under different post-treatment conditions is shown. Among them, the titanium alloy sample SLM-Ti6Al4V is a Ti6Al4V alloy that has been SLM-treated but not post-treated, and its average microhardness is 331.657HV; the titanium alloy sample HS300-Ti6Al4V is a Ti6Al4V alloy that has been heated to about 300℃ for heat treatment, and its average microhardness is 378.865HV; the titanium alloy sample HS1150-Ti6Al4V is a Ti6Al4V alloy that has been heated to about 1150℃ for heat treatment, and its average microhardness is significantly increased to 468.375HV; the titanium alloy sample HS1150-A-Ti6Al4V is a Ti6Al4V alloy that has been heated to about 1150℃ for heat treatment and annealing, and its average microhardness is 429.229HV.
[0072] It can be seen that the titanium alloy sample HS1150-A-Ti6Al4V has a certain hardness loss after annealing at high temperature, making its microhardness slightly lower than that of the titanium alloy sample S1150-Ti6Al4V directly treated at high temperature, but its microhardness is significantly higher than that of the titanium alloy sample after SLM treatment, that is, the hardness of the titanium alloy sample has been greatly improved. Thermal annealing can effectively reduce some residual stresses in the titanium alloy sample, and to a certain extent reduce the low plasticity and high brittleness caused by a large amount of α phase, while also improving the corrosion resistance of the titanium alloy sample. Further, titanium alloy samples of 10mm*10mm*4mm with different post-treatments were obtained for later electrochemical testing. Crystal glue, copper wire, and conductive copper foil tape were used for mounting. After mounting, the exposed sample surface was polished with 200 mesh, 400 mesh, 600 mesh, 800 mesh, 1200 mesh, 2000 mesh, and 3000 mesh sandpaper in turn. The sample was then immersed in a beaker filled with acetone and placed in an ultrasonic cleaning device for cleaning. After the ultrasonic cleaning, it was washed with deionized water and dried with a hair dryer. Electrochemical tests were performed using an electrochemical workstation, and the electrolyte was 3.5wt% NaCl solution. The reference electrode was an Ag / AgCl electrode. First, an open circuit potential test was performed for 6 hours to obtain a stable potential, and then a polarization curve test was performed with a test range of -0.3V to 1.2V, open circuit potential, and a scan rate of 0.1667mV / s.
[0073] like Figure 4 As shown, the horizontal axis (x-axis) represents the logarithm of the current density log(i), and the unit is nA / cm 2 ; The vertical axis (y-axis) represents the potential (E) in volts (V) relative to a silver / silver chloride (Ag / AgCl) reference electrode. Figure 4 In the figure, the titanium alloy sample SLM is a Ti6Al4V alloy that has been SLM-treated but not subjected to any post-treatment, and its test results are represented by a black curve; the titanium alloy sample HS300 is a Ti6Al4V alloy that has been heated to approximately 300°C for heat treatment, and its test results are represented by a red curve; the titanium alloy sample HS1150 is a Ti6Al4V alloy that has been heated to approximately 1150°C for heat treatment, and its test results are represented by a blue curve; the titanium alloy sample HS1150-A is a Ti6Al4V alloy that has been heated to approximately 1150°C for heat treatment and annealing, and its test results are represented by a green curve.
[0074] By comparing and analyzing the polarization curve results, the corrosion characteristics of four different samples under specific experimental conditions were obtained. Table 1 shows the corrosion potential (Ecorr / V) and corrosion current density (icorr / (nA / cm²)) of different titanium alloy samples.
[0075] Table 1 It can be seen from Table 1 that among all titanium alloy samples, titanium alloy sample HS1150-A exhibits the lowest corrosion current density of 23.61nA / cm², which has the best corrosion resistance. In contrast, the corrosion current density of titanium alloy sample SLM is the highest, reaching 61.86nA / cm², showing its relatively poor corrosion resistance.
[0076] That is to say, in general, the post-processing conditions of high-temperature stamping and post-annealing provided in the embodiments of the present invention can take into account the corrosion resistance and hardness of the titanium alloy sample on the basis of sacrificing a small amount of hardness and a trace amount of β-term content, and can complete the post-processing of the titanium alloy sample quickly and at low cost.
[0077] It should be understood that the cost and time consumption of hot stamping treatment are significantly reduced compared to hot static pressing treatment, and in the embodiment of the present invention, after the heating treatment is completed for the titanium alloy sample, the hot stamping treatment and annealing heat treatment will form a continuous production line mode. Under the condition of good temperature control and smooth progress, when entering the annealing heat treatment, the titanium alloy sample is still in a high temperature state, and there is no need to heat the titanium alloy sample twice. The annealing heat treatment can be directly performed after the hot stamping treatment, which minimizes energy consumption, speeds up the processing speed, and effectively improves the overall work efficiency. In addition, the embodiment of the present invention achieves a comprehensive improvement in hardness and corrosion resistance through a one-time comprehensive treatment, reduces the need for additional surface treatment or other enhancement measures, and saves related costs.
[0078] At the same time, the embodiment of the present invention also provides a dynamic control mechanism based on temperature difference, which monitors the actual temperature of the titanium alloy sample to verify the adaptability of the heat treatment parameters and the stamping processing parameters in actual applications. When the adaptability is low, the dynamic adjustment mechanism is triggered to flexibly respond to temperature errors, so that the heat treatment parameters and the stamping processing parameters form a tightly coupled and dynamically interactive relationship through the actual temperature of the titanium alloy sample after heat treatment, ensuring that the titanium alloy sample is only stamped under the optimal state, avoiding the phase composition that does not meet the expectations due to low temperature, and the organizational changes or deformation of the titanium alloy sample due to high temperature, thereby reducing the scrap rate caused by parameter mismatch, thereby saving the cost of titanium alloy raw materials.
[0079] In some embodiments, the dynamic adjustment mechanism includes compensatory heating, and the method also includes: when the actual temperature is lower than the heating temperature, calculating a first temperature difference between the actual temperature and the heating temperature; determining supplementary heat treatment parameters based on the first temperature difference, the supplementary heat treatment parameters including a supplementary heating temperature and a supplementary insulation time; placing the titanium alloy sample in a heat treatment zone, heating the titanium alloy sample according to the supplementary heating temperature, and when the titanium alloy sample is placed in the heat treatment zone for a period of time that reaches the supplementary insulation time, transferring the titanium alloy sample from the heat treatment zone to the stamping treatment zone; executing step S104.
[0080] Specifically, when the actual temperature is lower than the heating temperature, the temperature value that the titanium alloy sample needs to be heated to can be calculated based on the first temperature difference, and the temperature of the heat treatment zone is adjusted accordingly to the supplementary heating temperature to ensure that the titanium alloy sample reaches the required heating temperature, and the supplementary insulation time is adjusted based on the first temperature difference to ensure that the titanium alloy sample is evenly heated and achieves the required microstructural changes. The titanium alloy sample is placed back in the heat treatment zone and heated according to the supplementary heating temperature. When the insulation time reaches the supplementary insulation time, the titanium alloy sample is transferred from the heat treatment zone to the stamping treatment zone. During the transfer process, the actual temperature of the titanium alloy sample is monitored again to verify the adaptability of the heat treatment parameters and the stamping treatment parameters in actual applications, and corresponding operations are performed based on the adaptability to ensure that the heating treatment achieves the expected effect.
[0081] In some embodiments, the dynamic adjustment mechanism includes adjusting stamping process parameters, and the method also includes: when the actual temperature is higher than the heating temperature, calculating a second temperature difference between the actual temperature and the heating temperature; when the second temperature difference is within a first difference threshold, adjusting the stamping process parameters based on the actual temperature to obtain target stamping process parameters, and the target stamping process parameters are lower than the stamping process parameters; and stamping the titanium alloy sample in the stamping process area according to the target stamping process parameters to obtain a target titanium alloy sample.
[0082] Specifically, when the actual temperature is higher than the set heating temperature, if the second temperature difference is within the first difference threshold, the stamping process can be made more efficient and stable by fine-tuning the stamping processing parameters (such as stamping pressure, stamping speed, etc.), while avoiding the organizational changes or deformation of the titanium alloy sample caused by excessive temperature. Among them, the specific value of the first difference threshold depends on the type of titanium alloy sample, process requirements, etc., and the specific value can be flexibly set according to actual needs, and is not limited here.
[0083] It should be understood that selecting an appropriate stamping temperature can activate a specific phase change or plastic deformation mechanism of the titanium alloy specimen without causing significant shape changes. A higher temperature is conducive to reducing the yield strength of the titanium alloy specimen, making plastic deformation easier to occur while avoiding cold work hardening. A lower temperature can retain the high strength characteristics of the titanium alloy specimen, but requires a higher stamping pressure. For example, the first difference threshold may be set between 5°C and 20°C. Assuming that the set heating temperature is 1000°C and the actual temperature is 1005°C, the temperature difference is 5°C, which is within the first difference threshold. Based on the actual temperature of 1005°C, the stamping pressure or other parameters can be appropriately reduced to adapt to the higher initial temperature to ensure that the stamping process proceeds smoothly without affecting the performance of the titanium alloy specimen.
[0084] It should be understood that since the preset phase change parameter mapping table is determined based on the data of the pre-experiment, it is used to guide the phase change behavior of titanium alloy specimens at different temperatures. However, there may be certain errors in practical applications, which may be caused by differences between experimental conditions and production environments, changes in titanium alloy specimen batches, or other unforeseen factors. By real-time monitoring and adjustment of temperature and processing parameters, these errors can be effectively compensated to ensure that the titanium alloy specimen is always in the best processing state. If the actual temperature is lower than the set value, it may cause incomplete phase change or the phase composition does not meet expectations, affecting the performance of the titanium alloy specimen. Through the dynamic control mechanism, the heating temperature and holding time can be automatically adjusted when the temperature is detected to be low to ensure that the titanium alloy specimen reaches the required phase change conditions. Excessive temperature may cause the titanium alloy specimen to undergo organizational changes or deformation of the titanium alloy specimen under the initially obtained stamping processing parameters. The temperature can be monitored in real time and the stamping processing parameters (such as pressure, speed, etc.) can be adjusted to ensure that the titanium alloy specimen is processed within the appropriate temperature range.
[0085] In other words, the dynamic control mechanism based on temperature difference is used to ensure that the titanium alloy specimen is stamped in the best condition. It not only compensates for the potential errors in the preset phase change parameter mapping table, but also ensures that the phase composition and microstructure of the titanium alloy specimen meet expectations, avoiding unnecessary organizational changes or deformation. Through real-time monitoring and flexible adjustment, this mechanism significantly improves the stability of the production process and product quality.
[0086] In some embodiments, the S104 also includes: calculating the total oxygen content required to be supplied based on the surface area of the titanium alloy sample and the preset oxide layer thickness; obtaining the corresponding low-oxygen mixed gas based on the preset ratio of oxygen and inert gas and the total oxygen content; and supplying the low-oxygen mixed gas to the titanium alloy sample in the transfer path of the titanium alloy sample from the heat treatment zone to the stamping treatment zone.
[0087] Specifically, the hypoxic mixed gas is composed of oxygen and inert gas in a specific proportion. The total oxygen content is determined by the surface area of the titanium alloy sample and the thickness of the oxide layer. It is ensured that there is sufficient oxygen in the hypoxic mixed gas to react with the surface area of the titanium alloy sample. The total content of the inert gas is determined according to a preset proportion, and then a corresponding volume of uniformly mixed hypoxic mixed gas is obtained, in which the total content of the inert gas is significantly higher than the total content of oxygen.
[0088] A sufficient amount of oxygen is provided by the gas combination of the low-oxygen mixed gas to promote the formation of a thin and uniform oxide film on the surface of the titanium alloy sample, thereby enhancing the corrosion resistance of the titanium alloy sample. At the same time, the presence of a large amount of inert gas effectively inhibits excessive oxidation and avoids the degradation of the performance or surface defects of the titanium alloy sample caused by the oxidation reaction. That is to say, in the transfer process of the titanium alloy sample, the embodiment of the present invention controls the gas environment to which the titanium alloy sample is exposed by the inert gas to avoid chemical reactions between the titanium alloy sample and the elements in the air. Furthermore, in order to further improve the corrosion resistance of the titanium alloy sample, a small amount of oxygen is mixed in the inert gas to promote the controllable oxidation of the titanium alloy sample at high temperature to form a dense and stable titanium oxide layer. This oxide film can effectively prevent further oxidation and corrosion and play a good protective role.
[0089] For example, selecting an appropriate type of inert gas (such as argon or helium) and optimizing its ratio with oxygen can further improve the protection effect. Inert gas can not only dilute the oxygen concentration, but also form a stable gas barrier on the surface of the titanium alloy sample, reducing the impact of oxygen and other harmful gases in the outside air.
[0090] In some embodiments, the method further includes: when the second temperature difference is greater than the first difference threshold and less than the second difference threshold, before supplying the low oxygen mixed gas to the titanium alloy sample, performing low temperature treatment on the low oxygen mixed gas so that the low oxygen mixed gas reaches a preset temperature.
[0091] Specifically, if the second temperature difference is greater than the first difference threshold but less than the second difference threshold, the temperature difference is large, and before supplying the hypoxic mixed gas, it is first subjected to low temperature treatment to reach the preset temperature, and the titanium alloy sample is subjected to low temperature treatment by the low-temperature hypoxic mixed gas, and while being oxidized in a controlled manner, the actual temperature of the titanium alloy sample is accelerated to drop to the heating temperature to ensure the stamping treatment effect. Among them, the preset temperature can be determined according to the specific values of the first difference threshold and the second difference threshold, and the low temperature of the hypoxic mixed gas is used to accelerate the actual temperature of the titanium alloy sample to drop to the heating temperature, which is not limited here.
[0092] See also Figure 6 , Figure 6It is a schematic block diagram of a post-processing system for a laser selective melting additively manufactured component provided in an embodiment of the present invention. The post-processing system for a laser selective melting additively manufactured component can be configured in a server to execute the aforementioned post-processing system for a laser selective melting additively manufactured component.
[0093] like Figure 6 As shown, an embodiment of the present invention further provides a post-processing system 200 for a component manufactured by selective laser melting additive manufacturing, the system 200 comprising: The sample acquisition module 201 is used to obtain the initial ratio of the α phase and the β phase in the titanium alloy sample obtained by laser selective melting additive manufacturing; The processing parameter module 202 is used to obtain heat treatment parameters and stamping processing parameters according to the initial ratio of the α phase and the β phase based on a preset phase change parameter mapping table, wherein the preset phase change parameter mapping table includes: a data table of the change in the ratio of the α phase and the β phase in the titanium alloy under different heat treatment parameters and different stamping processing parameters, and the heat treatment parameters include heating temperature and holding time; the heating temperature belongs to the preset phase change temperature threshold range; A heating treatment module 203 is used to place the titanium alloy sample in a heat treatment zone, heat the titanium alloy sample according to the heating temperature, and transfer the titanium alloy sample from the heat treatment zone to a stamping treatment zone when the placement time of the titanium alloy sample in the heat treatment zone reaches the holding time; A sample transfer module 204, used for detecting the actual temperature of the titanium alloy sample during the transfer process of the titanium alloy sample from the heat treatment area to the stamping treatment area; The stamping processing module 205 is used to, when the actual temperature reaches the heating temperature, perform stamping processing on the titanium alloy sample in the stamping processing area according to the stamping processing parameters, and perform annealing processing on the titanium alloy sample after the stamping processing to obtain a target titanium alloy sample, wherein the target ratio of α phase to β phase in the target titanium alloy sample is lower than the initial ratio.
[0094] Exemplarily, the post-processing system 200 for manufacturing components by selective laser melting additive manufacturing further includes: a first temperature difference module, a supplementary heat treatment module, and a supplementary heating module.
[0095] A first temperature difference module, used for calculating a first temperature difference between the actual temperature and the heating temperature when the actual temperature is lower than the heating temperature; A supplementary heat treatment module, used to determine supplementary heat treatment parameters according to the first temperature difference, wherein the supplementary heat treatment parameters include supplementary heating temperature and supplementary heat preservation time; A supplementary heating module is used to place the titanium alloy sample in a heat treatment zone, heat the titanium alloy sample according to the supplementary heating temperature, and transfer the titanium alloy sample from the heat treatment zone to the stamping treatment zone when the placement time of the titanium alloy sample in the heat treatment zone reaches the supplementary insulation time; and execute the sample transfer module 204.
[0096] Exemplarily, the post-processing system 200 for manufacturing components by selective laser melting additive manufacturing further includes: a second temperature difference module, a stamping adjustment module, and an optimized stamping module.
[0097] A second temperature difference module, used for calculating a second temperature difference between the actual temperature and the heating temperature when the actual temperature is higher than the heating temperature; a stamping adjustment module, configured to adjust a stamping process parameter based on the actual temperature to obtain a target stamping process parameter when the second temperature difference is within a first difference threshold, wherein the target stamping process parameter is lower than the stamping process parameter; The optimized stamping module is used to perform stamping processing on the titanium alloy sample in the stamping processing area according to the target stamping processing parameters to obtain the target titanium alloy sample.
[0098] Exemplarily, the sample transfer module 204 further includes: an oxygen content submodule, a gas acquisition submodule, and a low oxygen supply submodule.
[0099] An oxygen content submodule, used for calculating the total oxygen content required to be supplied according to the surface area of the titanium alloy sample and the preset oxide layer thickness; A gas acquisition submodule, used for acquiring a corresponding hypoxic mixed gas according to a preset ratio of oxygen to inert gas and the total oxygen content; The low oxygen supply submodule is used to supply the low oxygen mixed gas to the titanium alloy sample in the transfer path of the titanium alloy sample from the heat treatment area to the stamping treatment area.
[0100] Exemplarily, the post-processing system 200 for laser selective melting additively manufactured components also includes: a low-temperature treatment module, which is used to perform low-temperature treatment on the low-oxygen mixed gas before supplying the low-oxygen mixed gas to the titanium alloy sample when the second temperature difference is greater than the first difference threshold and less than the second difference threshold, so as to make the low-oxygen mixed gas reach a preset temperature.
[0101] Exemplarily, the stamping process parameters include stamping rate, stamping pressure, and holding time; wherein the stamping rate is 300 mm / s to 500 mm / s, the stamping pressure is 10 MPa, and the holding time is 10 s.
[0102] Exemplarily, the preset phase change temperature threshold is 980°C to 1200°C.
[0103] Exemplarily, the stamping processing module 205 also includes: a first annealing submodule, which is used to adjust the temperature of the titanium alloy sample to a first preset annealing temperature threshold, and keep it warm for a preset annealing time, and anneal the titanium alloy sample at a preset cooling rate to obtain the target titanium alloy sample.
[0104] Exemplarily, the stamping processing module 205 also includes: a second annealing sub-module, used to adjust the temperature of the titanium alloy sample to a second preset annealing temperature threshold, and keep it at a third preset annealing temperature threshold for a preset annealing time, cool the titanium alloy sample for annealing, and obtain the target titanium alloy sample, wherein the second preset annealing temperature threshold is higher than the third preset annealing temperature threshold.
[0105] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A post-processing method for a laser selective melting additive manufacturing component, characterized in that: The method comprises: S101 obtains the initial ratio of α phase and β phase in the titanium alloy sample obtained by laser selective melting additive manufacturing; S102, based on a preset phase change parameter mapping table, obtaining heat treatment parameters and stamping processing parameters according to the initial ratio of the α phase and the β phase, wherein the preset phase change parameter mapping table includes: a data table of changes in the ratio of the α phase and the β phase in the titanium alloy under different heat treatment parameters and different stamping processing parameters, the heat treatment parameters include heating temperature and heat preservation time; the heating temperature belongs to the preset phase change temperature threshold range; S103: placing the titanium alloy sample in a heat treatment zone, heating the titanium alloy sample according to the heating temperature, and when the titanium alloy sample is placed in the heat treatment zone for a time period that reaches the heat preservation time period, transferring the titanium alloy sample from the heat treatment zone to a stamping treatment zone; S104, during the process of transferring the titanium alloy sample from the heat treatment zone to the stamping treatment zone, detecting the actual temperature of the titanium alloy sample; S105 When the actual temperature reaches the heating temperature, the titanium alloy sample is stamped in the stamping area according to the stamping parameters, and the stamped titanium alloy sample is annealed to obtain a target titanium alloy sample, wherein a target ratio of α phase to β phase in the target titanium alloy sample is lower than the initial ratio.
2. The method according to claim 1, characterized in that The method further comprises: When the actual temperature is lower than the heating temperature, calculating a first temperature difference between the actual temperature and the heating temperature; Determining supplementary heat treatment parameters according to the first temperature difference, wherein the supplementary heat treatment parameters include supplementary heating temperature and supplementary heat preservation time; The titanium alloy sample is placed in a heat treatment zone, and heated according to the supplementary heating temperature. When the titanium alloy sample is placed in the heat treatment zone for a period of time that reaches the supplementary insulation period, the titanium alloy sample is transferred from the heat treatment zone to the stamping treatment zone; and step S104 is executed.
3. The method according to claim 1, characterized in that The method further comprises: When the actual temperature is higher than the heating temperature, calculating a second temperature difference between the actual temperature and the heating temperature; When the second temperature difference is within the first difference threshold, adjusting the stamping process parameter based on the actual temperature to obtain a target stamping process parameter, the target stamping process parameter being lower than the stamping process parameter; The titanium alloy sample is subjected to stamping treatment in the stamping treatment area according to the target stamping treatment parameters to obtain a target titanium alloy sample.
4. The method according to any one of claims 1 to 3, characterized in that: The S104 further includes: Calculate the total oxygen content required to be supplied according to the surface area of the titanium alloy sample and the preset oxide layer thickness; obtain the corresponding hypoxic mixed gas according to the preset ratio of oxygen and inert gas and the total oxygen content; The low-oxygen mixed gas is supplied to the titanium alloy sample in a transfer path of the titanium alloy sample from the heat treatment zone to the press treatment zone.
5. The method according to claim 4, characterized in that The method further includes: when the second temperature difference is greater than the first difference threshold and less than the second difference threshold, before supplying the low oxygen mixed gas to the titanium alloy sample, performing low temperature treatment on the low oxygen mixed gas so that the low oxygen mixed gas reaches a preset temperature.
6. The method according to claim 3, characterized in that The stamping processing parameters include stamping rate, stamping pressure, and holding time; wherein the stamping rate is 300 mm / s to 500 mm / s, the stamping pressure is 10 MPa, and the holding time is 10 s.
7. The method according to claim 1, characterized in that The preset phase change temperature threshold is 980°C to 1200°C.
8. The method according to claim 1, characterized in that: The S105 further includes: The temperature of the titanium alloy sample is adjusted to a first preset annealing temperature threshold, and maintained at a preset annealing time, and the titanium alloy sample is annealed at a preset cooling rate to obtain the target titanium alloy sample.
9. The method according to claim 1, characterized in that: The S105 further includes: The temperature of the titanium alloy sample is adjusted to a second preset annealing temperature threshold, and maintained at a third preset annealing temperature threshold for a preset annealing time, and the titanium alloy sample is cooled for annealing to obtain the target titanium alloy sample, wherein the second preset annealing temperature threshold is higher than the third preset annealing temperature threshold.
10. A post-processing system for a laser selective melting additive manufacturing component, characterized in that: The system comprises: A sample acquisition module is used to obtain the initial ratio of α phase and β phase in the titanium alloy sample obtained by laser selective melting additive manufacturing; A processing parameter module, for obtaining heat treatment parameters and stamping processing parameters according to the initial ratio of the α phase and the β phase based on a preset phase change parameter mapping table, wherein the preset phase change parameter mapping table includes: a data table of the change in the ratio of the α phase and the β phase in the titanium alloy under different heat treatment parameters and different stamping processing parameters, the heat treatment parameters include heating temperature and holding time; the heating temperature belongs to the preset phase change temperature threshold range; A heating treatment module, used for placing the titanium alloy sample in a heat treatment zone, heating the titanium alloy sample according to the heating temperature, and transferring the titanium alloy sample from the heat treatment zone to a stamping treatment zone when the placement time of the titanium alloy sample in the heat treatment zone reaches the insulation time; A sample transfer module, used for detecting the actual temperature of the titanium alloy sample during the transfer process of the titanium alloy sample from the heat treatment area to the stamping treatment area; A stamping processing module is used to, when the actual temperature reaches the heating temperature, perform stamping processing on the titanium alloy sample in the stamping processing area according to the stamping processing parameters, and perform annealing processing on the titanium alloy sample after the stamping processing to obtain a target titanium alloy sample, wherein the target ratio of α phase to β phase in the target titanium alloy sample is lower than the initial ratio.
Citation Information
Patent Citations
Method for reducing residual stress of additive manufacturing high-temperature alloy based on hot isostatic pressing
CN116275041A